2004
DOI: 10.1007/s00221-004-1924-z
|View full text |Cite
|
Sign up to set email alerts
|

Can prepared responses be stored subcortically?

Abstract: Quick voluntary responses to environmental stimuli are required of people on a daily basis. These movements have long been thought to be controlled via cortical loops involving processing of the stimulus and generation of a suitable response. Recent experiments have shown that in simple reaction time (RT) tasks, the appropriate response can be elicited much earlier (facilitated) when the "go" signal is replaced by a startling (124 dB) auditory stimulus. In the present experiment we combined a startling acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 17 publications
13
167
3
1
Order By: Relevance
“…For reasons unrelated to startle, some dual-task experiments utilize choice-reaction time paradigms where more than one response alternative exists instead of the simple reaction time paradigm utilized in the current study. In motor control literature, movements produced during choice reaction time para- digms are inconsistently influenced by StartReact effects compared with the highly robust results observed when producing the same movement in simple reaction time paradigms (Carlsen et al 2004(Carlsen et al , 2011. Thus, although the full extent of StartReact effects in dual-task scenarios remains unclear, the possibility for StartReact effects to interact with voluntary movements during dual-task paradigms alone warrants further examination.…”
Section: Discussionmentioning
confidence: 97%
“…For reasons unrelated to startle, some dual-task experiments utilize choice-reaction time paradigms where more than one response alternative exists instead of the simple reaction time paradigm utilized in the current study. In motor control literature, movements produced during choice reaction time para- digms are inconsistently influenced by StartReact effects compared with the highly robust results observed when producing the same movement in simple reaction time paradigms (Carlsen et al 2004(Carlsen et al , 2011. Thus, although the full extent of StartReact effects in dual-task scenarios remains unclear, the possibility for StartReact effects to interact with voluntary movements during dual-task paradigms alone warrants further examination.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Forgaard et al (2011) found participants released motor acts whose amplitude fell between targets when 5 their movements were triggered by LAS. In contrast, however, some authors failed to detect any facilitation of movement initiation in tasks where participants had multiple movement choices (Carlsen et al, 2004). Thus, it seems that under certain circumstances, this relatively simple technique may be able to provide a readout of the state of motor preparation slightly prior to the voluntary decision to move.…”
Section: Introductionmentioning
confidence: 88%
“…Since a similar difference (18 ms average) in onset latencies between the sled acceleration-only and tone-only trials was observed in the present experiment (Table 6), the combination of the stimuli appears to be responsible for the advanced muscle onset time. Advanced onset times have been observed in acoustically startled volunteers performing simple reaction-time tasks (9,10,30,37) and are reportedly shifts from voluntary latencies to startle reflex latencies. Similarly, the advanced muscle responses to the combined stimuli could suggest that the startle initiates a faster execution of the neural responses triggered by a sudden whole body forward acceleration.…”
Section: Summation Of the Startle And Sled Perturbation Stimulimentioning
confidence: 99%